Epileptic Seizure: An Atypical Presentation in Brucellosis - Simin-Dokht Shoaei; Mohamad Farahbakhsh; Mehrdad Haghighi; Fahime Hadavand (Case Reports in Clinical Practice, 2017)
Neurologic involvement occurs in approximately 10% cases of brucellosis and is a serious complication. It manifests with unique and some rare manifestations. We present the first patient with seizures in Brucella meningitis without encephalitis, space-occupying lesion, or vascular involvement. The patient is a 23-year-old man with complaint of seizure. He had generalized weakness for 2 weeks before. In 1st day of admission, he had the second convulsion. Cerebrospinal fluid (CSF) on admission showed lymphocytic pleocytosis and high protein. Brain magnetic resonance imaging and computed tomography scan were normal. Further evaluations resulted a positive Wright, Coombs’ Wright, and 2- mercaptoethanol (2ME) tests. Specific regimen with rifampin, doxycycline, and ceftriaxone in the 1st month then the first two with trimethoprimsulfamethoxazole (TMP-SMX) for 5 months administered. 6 months after completion of treatment in follow-up he has no seizure, systemic or localized symptoms.